Potential of Cistus ladanifer L. (rockrose) in small ruminant diets – effect of season and plant age on chemical composition, in vitro digestibility and antioxidant activity. (6th August 2015) - Guerreiro, O.; Dentinho, M. T. P.; Moreira, O. C.; Guerra, A. R.; Ramos, P. A. B.; Bessa, R. J. B.; Duarte, M. F.; Jerónimo, E.
Abstract: Shrubs can provide an important contribution to the fodder resources for small ruminants in Mediterranean areas, but there is limited information on their feed value, including secondary metabolites and their seasonal differences. This study evaluated the effect of seasonal variation in chemical composition, in vitro digestibility and antioxidant activity of the aerial parts of plants of Cistus ladanifer of two age groups [young plants vs. older ones (2–6 years old)]. Aerial parts of C. ladanifer plants of both age groups were characterized by moderate cell‐wall content [321–410 g NDF kg −1 dry matter (DM)], high levels of phenolic compounds (55·1–106 g gallic acid equivalents per kg DM) and condensed tannins (CT) (32·1–161 g kg −1 DM), low protein content (55–100 g kg −1 DM) and low digestibility (249–315 g of digestible organic matter per kg DM). During autumn and winter, C. ladanifer showed higher protein levels and lower cell‐wall content than in the other seasons. The highest values of phenolic compounds, CT and antioxidant activity were achieved during summer. Young plants showed higher levels of phenolic compounds during spring, summer and winter, and higher CT contents in summer (more than 54 g kg −1 DM) compared to old plants. Aerial parts of C. ladanifer of both age groups may be used as a component of ruminant nutrition, but only as a supplement and associated with other feeding resources to complement its nutritional imbalances.